Identiti Bidayuh Sarawak dalam tarian Langgie Pingadap - Magiman, Mohamad Maulana; Salleh, Norhuda (University of Malaya, 2017)
Langgie Pingadap dance was performed by ethnic Bidayuh Bukar in Sarawak after harvest work performed as a prayer of gratitude to God on the yield obtained. Langgie Pingadap dance is a reflection identity of the Bidayuh community that often associated with hill paddy farming activities. It is appropriate for the life of this community, also known as the Land Dayaks who inhabit the land and run hill paddy farming. This study identified the Bidayuh community identity through Langgie Pingadap dance movement and also study the symbols used in the dance itself. To achieve the objectives of the research, ethnographic methods was used in this study. This method focuses on social phenomena from the perspective of the involvement of researchers and respondents were implemented. This study found that the identity featured by the Bidayuh dance adapted from their lives as rice farmers hill. The elements of unification clearly shown in every dance performed. The use of the symbol is highlighted by the selection of colour in clothes of black as the base colour, red and yellow as the colour combination. Besides the clothing also graced with floral motifs and decoration which means leading to the formation of the identity of the Bidayuh. The modernization also has allowed this dance continues to be practiced but with some modifications based on changes in people's confidence in the practitioner. In the past time, this dance once performed among the Bidayuh farmers only, but now it has been presented during the Gawai festival each year. The meaning of this dance in the Gawai festival is to welcome the guests and the spirit of joint action between the guest and the host.